Regular patterns of play in the counterattacks of the FC Barcelona and Manchester United FC football teams - Sarmento, H.; Barbosa, A.; Campanico, J.; Anguera, M. T.; Leitao, J. (World Congress of Performance Analysis of Sport IX, 2012)
The aim of the present study is to demonstrate the potential of the software THÈME 5.0, for the detection of behavior temporal patterns (T-pattern) in the football game, more specifically, in the actions of counterattack of the FC Barcelona (FCB) and Manchester United (MU). The sample consisted of 24 football games (12 per team) of domestic competitions that were analyzed by systematic observation, using the observational instrument developed by Sarmento et al. (2010). The study of the data reliability was calculated by the intra and inter observer agreement and values above .90 were achieved for all the criteria. The data were analyzed through the use of the software THÈME 5.0. The results show that many temporal patterns exist in soccer. The number, frequency and complexity of the detected patterns indicate that sport behavior is more synchronized than the human eye can detect. We selected 8 t-patterns (4 per team), in relation to different phases of the counterattack that were analyzed in a detailed way during the presentation. We can conclude, in a general way, that there is a similar feature in the selected BA t-patterns, i.e., the sequences start through an interception of the ball in the left corridor (zone 6) in terms of numerical superiority, after that, there was a quick transfer of the game center, from the right to the left, trying to take advantage, probably, of the imbalance of the opposing defensive structure (numerical equality). The sequences are developed through actions like the conduction of the ball with the intention of displacing the center of the game in the field of the game, to the areas close to the penalty area. In relation to the analysis of the sequences that end through a shot with a scored goal allowed us to understand (beyond the fact that these sequences are developed by the left corridor) that these shots are performed in the central zone of the offensive sector (zone 11) in conditions of numerical inferiority. In a similar way, the selected MU T-patterns showed that the sequences of the counter-attacks start in the central zone of the defensive midfield (zone 5), in a context of numerical superiority, and are developed in the left corridor through actions like the short pass to forward, the diagonal pass forward, and reception/control of the ball, in contexts of numerical equality. The last pass came from the left corridor (zone 7), and the sequences finished in the central zone of the offensive midfielder (zone 8 and 11), through a shot inside or a shot with a scored goal. This type of analysis allows us to know and to characterize the regular structures of offensive sequences in football teams. The t-patterns detected in these successful teams allowed us to know how that process is developed in an effective way. This information is relevant, on the one hand for the team itself because it makes it possible to conceive training exercises in order to increase this efficiency, and on the other hand it allows, for example, that the opposing coaches can develop strategies to prevent that the BA and MU teams perform these transitions effectively.